Cost variation analysis of oral anti-diabetic agents available in Indian market - Gedam, Sanjay; Barmaiya, Namita (International Journal of Basic & Clinical Pharmacology, 2021)
Background: The objective of this study was to analyze cost variations of oral antidiabetic drugs available in Indian market. Methods: An observational study was carried out using CIMS (current index of medical specialities), (July 2020 to October 2020) and 1 mg.com, where difference in the maximum and minimum price of a particular drug, manufactured by different pharmaceutical companies, in the same strength, number and dosage form was compared and the percentage variation in price was calculated. Data was analyzed using descriptive statistical analysis. Results: The minimum and maximum percentage price variation for different classes of drugs respectively is as follows- in single drug therapy, the price variation between a sulfonylurea group of drugs glibenclamide (5 mg) shows maximum price variation of 400%, while glipizide (2.5 mg) shows variation of 81.8%. In biguanides, thizolidinediones and DPP4 inhibitor groups of drugs, metformin (500 mg), pioglitazone (30 mg) and vildagliptin show maximum price variation of 334.78%, 307 % and 264.6% respectively. In α- glucosidases inhibitor group of drugs voglibose (0.2 mg) shows maximum price variation of 284%. In meglitinides group of drugs, nateglinide (60 mg) shows maximum price variation of 284.6 %. In combination drug therapy, glimepiride and metformin combination (2+500 mg SR) shows the maximum variation up to 352.8%. Conclusions: The percentage cost variation of different brands of the same drug manufactured in India is very wide and the reason behind marketing a drug should be directed towards maximizing the benefit of therapy and minimizing negative personal and economic consequences.